A Wrap Around Approach to Suicide Prevention in Schools: It’s not just School Counselors…. - Tahani Dari; Jan Gay (Teaching and Supervision in Counseling, 2022)
The prevalence of suicide among children and adolescents is alarming. According to the Centers for Disease Control and Prevention (2020), suicide is the second leading cause of death among youth ages 10-19. Schools are one of the main providers of mental health support for students (O’Neill et al., 2021). Similar to school-based mental health counselors, psychologists, and social workers, school counselors are trained and prepared in suicide risk assessment and intervention. Mental health issues, however, require collaborative approaches that address the complex factors impacting youth, such as the impact of the dual pandemics of COVID-19 and racial injustice. The purpose of this article is to enhance considerations offered by Gallo and Wachter-Morris (2022) in their article, “Suicide intervention in schools: If not school counselors, then who?” by positioning a wrap-around approach as a necessary component of culturally responsive suicide assessment and intervention and to provide training implications for counselor educators.
Keywords: wraparound services; suicide intervention; school counseling; multicultural considerations